Locus amoenus : gardens and horticulture in the Renaissance - Samson, Alexander (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, 2012)
Locus Amoenus provides a pioneering collection of new perspectives on Renaissance garden history, and the impact of its development. Experts in the field illustrate the extent of our knowledge of how the natural world looked and how humans related to their environment. A ground-breaking collection of new perspectives on garden historyEssays demonstrate the extent of our knowledge of how the natural world looked and how humans related to their environmentThe book's broad coverage includes botany and herbals, literary reflections of changing ideas of landscape and nature, and human's place within.
Introduction: Locus amoenus : gardens and horticulture in the Renaissance / Alexander Samson -- The world of the Renaissance herbal / Brent Elliott -- Clinging to the past : medievalism in the English "Renaissance" garden / Paula Henderson -- River gods : personifying nature in sixteenth-century Italy / Claudia Lazzaro -- Dissembling his art : "Gascoigne's Gardnings" / Susan C. Staub -- "My innocent diversion of gardening" : Mary Somerset's plants / Jennifer Munroe -- Outdoor pursuits : Spanish gardens, the "huerto," and Lope de Vega's Novelas a Marcia Leonarda / Alexander Samson -- Experiencing the past : the archaeology of some Renaissance gardens / Brian Dix.
Includes bibliographical references and index.
Print version record.
Keywords: 1450-1600; Gardens -- Europe, Western -- History -- 16th century; Gardens -- Social aspects -- Europe, Western -- History -- 16th century; Gardening -- Europe, Western -- History -- 16th century; Horticulture -- Europe, Western -- History -- 16th century; Gardens, Renaissance -- History; Gardens in literature; European literature -- Renaissance, 1450-1600 -- History and criticism; Renaissance; GARDENING -- Regional -- General; European literature -- Renaissance; Gardening; Gardens; Gardens in literature; Gardens, Renaissance; Gardens -- Social aspects; Horticulture; Intellectual life; Manners and customs; Renaissance; Europe, Western -- Social life and customs -- 16th century; Europe, Western -- Intellectual life -- 16th century; Europe, Western; Electronic books; Criticism, interpretation, etc; History